PENGARUH GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP MOTIVASI KERJA PEGAWAI : Kajian terhadap Karyawan di Lingkungan Dinas Pendidikan Propinsi Jawa Barat - Rusman (2013)
Iri the leadership theories, particularly in relation with the behaviorai theories, the leadership is meant by a set of behaviorai descriptions in doing interactions with the staff. The leadership behaviors are indicated by descriptionof leader's persoriality include: (1) social maturity, (2) intelligence, (3) needs of achieve- ment, and (4) attitude for human relation. The form of personality behavior really form the leadership characteristics or the dominant leadership behaviour. The objective of instituional leadership is to achieve the goals of organization, or to maintain the group of persons in order to save the existence of organization. The influence of the leadership for the maintenance of group, for examples, can be explorated to their relation with the satisfaction and motivation in doing tasks. The problem of research can be formulated as in the following: How much the influence of leadership and work satisfaction on work motivation of employee? The location of research is in the office of Educational Official of West Java Province, with the total respondents of research was 155 employees. In accordance with the problem of research, so that it's used descriptive method with path analysis technique to analyze data. On the base of quantitave data analysis, the finding of research in general can be formulated about the influence of the leadership style and work satisfaction on work motivation as in the following: First, the influence magnitude of joint variables of Xi and X2 on varible Y is significant (ti = 6.784, t2 = 4.907 > t.95:i52 = 2.576); the magnitude of pool influence is 0.669, beside of epsilon variable 0.575. It means that the leadership style and work satisfaction have the joint influence on the work motivation about 66.9%, while the other variables beside the leadership style and work satisfaction have the magnitude of influence about 57.5%. Second, the infiuence magnitude of variable X on variable Y is significant (t = 15.726 > to.95: 153) is 0.786, beside the magnitude influence of epsilon variable 0.618. It means that the work motivation influenced by the leadership style about 78.8%, while the other variables beside the leadership style influence about 61.8%. Third, the magnitude of influence of variable Xi on variableX2 is significant (t = 15.268 > to.95; 153) is 0.777, beside the influence of epsilon variable 0.629. It means that the work satisfaction influenced by leadership style about 77.7%, while the influence beside the influence magnitide of leadership style is 62.95%. Finally, the magnitude of influence of variable X2 on variable Y is significant (t = 14.242 > to.95: 153) is 0.755, beside the magnitude of epsilon variable 0.656. It means that the work motivation influenced by the work satisfaction is about 75.5%, while the influence of the other variables beside the magnitude of the work satisfaction influence about 65.57%.